2016
DOI: 10.1109/jphot.2016.2523993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intercore Crosstalk on the Transmission Distance of QAM Formats in Multicore Fibers

Abstract: We investigate the impact of intercore crosstalk on the achievable transmission distance of three square quadrature amplitude modulation (QAM) formats. We show that increasing intercore crosstalk across an 18 dB range starting from −43.4 dB/100 km reduces the achievable transmission distance for all formats, with a greater impact on higher order modulation formats. For a crosstalk level arising from equal signal launch power in each core of a homogeneous 7-core fiber, we measure a reduced transmission distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…The back-to-back MI achieved for PDM-4QAM, PDM-16QAM and PDM-64QAM was 4, 8 and 11.98 bits/s/Hz respectively. At these distances (110, 40 and 10 spans) a XT level of -32.2dB/100km (corresponding to the same launch power in all cores [6]), the achievable rate drops by 1.4% for PDM-4QAM, 1% for PDM-16QAM and 0.2% for PDM-64QAM. If a loss of 7% in acheiable rate is permitted XT can be increased to -26, -25.2 and -19 dB/100km, for 4QAM, 16QAM and 64QAM respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The back-to-back MI achieved for PDM-4QAM, PDM-16QAM and PDM-64QAM was 4, 8 and 11.98 bits/s/Hz respectively. At these distances (110, 40 and 10 spans) a XT level of -32.2dB/100km (corresponding to the same launch power in all cores [6]), the achievable rate drops by 1.4% for PDM-4QAM, 1% for PDM-16QAM and 0.2% for PDM-64QAM. If a loss of 7% in acheiable rate is permitted XT can be increased to -26, -25.2 and -19 dB/100km, for 4QAM, 16QAM and 64QAM respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that a cross talk (XT) of less than -32.2dB/100km can reduce transmission distances by up to 40% [6]. Since XT can be engineered to any required level, here we investigate how it affects the achievable rate of MCF transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum reach obtained for each MCF is shown in Table II, where a 4-dB margin has been considered similarly to the nonlinear propagation case. Recently, a more sophisticated method of estimating the impact of ICXT based on its random nature has been proposed [18]. It has been shown, however, that estimations based on average ICXT may be too optimistic.…”
Section: Transmission Reach Estimationmentioning
confidence: 99%
“…Such a configuration would allow for 6 cores for QKD and 13 cores for classical WDM coherent signals. The crosstalk has been shown to be dominated by the neighboring cores [3], which is why we can avoid loading all the cores to reduce the equipment demand.…”
Section: Experimental Setup and Measurement Proceduresmentioning
confidence: 99%